C. acnes qPCR-Based Antibiotics Resistance Assay (ACQUIRE) Reveals Widespread Macrolide Resistance in Acne Patients and Can Eliminate Macrolide Misuse in Acne Treatment - Zhang, Jingheng; Yu, Fang; Fu, Keyun; Ma, Xinyu; Han, Yi; Ali, Chi Ching; Zhou, Haonan; Xu, Yantao; Zhang, Tingyue; Kang, Shuntong; Xu, Yiming; Li, Zhuolin; et al. (Frontiers in Public Health, 2022)
Background: Macrolides have been widely used to treat moderate-to-severe acne for more than 50 years. However, prevalent antibiotic resistance of Propionibacterium acnes, along with the absence of clinically available resistance tests, has made macrolide misuse a frequent occurrence around the globe, with serious consequences. Objective: We developed C. acnes qPCR-based antibiotics resistance assay (ACQUIRE) to enable fast and accurate detection of C. acnes macrolide resistance in clinical settings, representing an opportunity to administer antibiotics more wisely and improve the quality of care. Methods: A cross-sectional observational study (n=915) was conducted to probe into the macrolide resistance of C. acnes in acne patients. Results: The high sensitivity of ACQUIRE enabled us to reveal a much higher C. acnes 23S rDNA point mutation rate (52%) and thus a higher macrolide resistance (75.5%) compared to previous reports. Carriage of ermX gene was discovered on 472 (53%) subjects, which concurs with previous studies. Conclusion: Macrolide resistance of C. acnes is much higher than previously reported. Integrating ACQUIRE into acne treatment modalities may eliminate macrolide misuse and achieve better clinical improvements.